Carnosol Improved Lifespan and Healthspan by Promoting Antioxidant Capacity in Caenorhabditis elegans. (24th June 2019) - Lin, Chunxiu; Zhang, Xiaoying; Su, Zuanxian; Xiao, Jie; Lv, Muwen; Cao, Yong; Chen, Yunjiao
Abstract : Carnosol, a phenolic diterpene, is one of the main constituents of Rosmarinus . It is known to possess a range of bioactivities, including antioxidant, anticancer, antimicrobial, and anti-inflammatory properties. Nevertheless, the antiaging effects of carnosol have received little attention. This study first indicated that carnosol increased the healthspan of Caenorhabditis elegans ( C. elegans ). First, compared with the control condition, carnosol treatment effectively decreased ROS accumulation under normal or oxidative stress condition, significantly increased several key antioxidant enzyme activities, and significantly decreased MDA content. Second, carnosol effectively prolonged lifespan under normal and stress conditions and slowed aging-related declines, including mobility, age pigmentation, and neurodegenerative disease, but had no effect on fertility and fat deposition. Finally, carnosol-mediated longevity required the upregulated expression of sod-3, sod-5, hsf-1, hsp-16.1, and hsp-16.2 and was dependent on the hsf-1 gene. Increased DAF-16 translocation was observed, but daf-16 was independent of the effects on lifespan induced by carnosol. These results suggested that carnosol might serve as a good source of natural antioxidants, and in particular, carnosol could be explored as a potential dietary supplement to slow aging.